Exploration into the relationship between managers' sensemaking and CSR outcomes - Jackson, Sharon M. (Cranfield University, 2009)
This study aims to understand the relationship between managers’ sensemaking of their organisations’ espoused Corporate Social Responsibility (CSR) intentions and outcomes through asking: 1. How do managers make sense of the CSR intentions espoused by their organisations? 2. What are the outcomes of the sensemaking process? 3. To what extent are these outcomes congruent with the organisations’ espoused CSR intentions? The reason for this research is because organisations are struggling to integrate their espoused CSR into daily business processes and are being criticised for a gap between rhetoric and action by stakeholders. The sector chosen for this study is the electronic consumer products industry because it has a potentially huge impact on the environment and society and is starting to engage in CSR. There are few empirical studies on CSR in this sector. This exploratory, qualitative, empirical study uses a case study approach to collect data through focus group dialogue which is analysed through Conversation Analysis. Two main findings are 1. Managers’ sensemaking processes can lead to ‘no action’ in terms of embedding espoused CSR intentions. 2. Organisational culture impacts on CSR outcomes. Furthermore, managers do not read their organisations’ CSR communications. A limitation of this research is that just two cases and fifteen participants were studied. Future research is necessary to explore suggestions emerging from the findings. This study makes a contribution to theory, in that ‘no action’, status quo is a possible outcome of sensemaking, and also contributes theoretical insight into the phenomenon of the interrelationship between organisational sensemaking and individual sensemaking.